Spontaneous and Drug-induced Arteritis/Polyarteritis in the Göttingen Minipig—Review. (February 2018) - Dincer, Zuhal; Piccicuto, Virginie; Walker, Ursula Junker; Mahl, Andreas; McKeag, Sean
Arteritis/polyarteritis occurs spontaneously in many species used in preclinical toxicology studies. In Göttingen minipigs, arteritis/polyarteritis is an occasionally observed background change. In the minipig, this finding differs in frequency and nature from age-related polyarteritis nodosa in rats or monkeys, and Beagle pain syndrome in dogs. In minipigs, it can be present in a single small- or medium-sized artery of an organ or a few organs and is most commonly recorded in the cardiac and extracardiac blood vessels, vagina, oviduct, rectum, epididymis, spinal cord, pancreas, urinary bladder, kidneys, and stomach. The etiology is unknown although it has been considered in minipigs as well as in rats, dogs, and monkeys to be possibly immune mediated. This background change is important with respect to its nature and distribution in the minipig in order to distinguish it from drug-induced vascular changes, which might occur in similar locations and have similar morphologic features. This review summarizes the morphology, incidence, and predilection sites of arteritis as a spontaneously occurring background change and as a drug-induced vasculopathy in the minipig, and also describes the main aspects to consider when evaluating vascular changes in Göttingen minipig toxicity studies and their human relevance.